Influence of Crack Parameters and Loading Direction on Buckling Behavior of Cracked Plates Under Compression - Saleh, Nathera Abdual Hassan (Basrah Journal for Engineering Sciences, 2011)
The aim of the present paper is to investigate buckling phenomenon of various cracked plates under compression load. The finite element procedure (ANSYS Package) is used to determine the critical buckling load by considering the effects of crack length and crack location (i.e. crack parameters) as well as loading direction parallel or perpendicular with respect to crack faces. It is found from the obtained results which are summarized graphically in figures that the crack parameters and loading direction have significant effects on the critical buckling load (i.e. increased or decreased) of compressed cracked plates. The effects of these factors are discussed in detail. The useful and interesting conclusions drawn from this work will be helpful for health monitoring or condition assessment of aging plated structures with cracking damages.